A Preliminary Randomized, Single‑blinded, Placebo‑controlled Clinical Dose–response Study to Elucidate the Effect of Ongoing Isometric Contraction of Muscles on the Vital Capacity of Lungs on Administering Blatta orientalis - Kushwaha, U; Supriya, G; Nair, B; Chattopadhyay, K; Nair, A; Vishwakarma, S (Wolters Kluwer Medknow Publications, 2022)
Introduction: Blatta orientalis is an indicated remedy for asthma and other chronic obstructive pulmonary diseases in homeopathic medicine. Preclinical studies indicate that B. orientalis shows anti-asthmatic properties in animals when induced with bronchospasm using acetylcholine through nonselective anticholinergic and antihistaminic activities. However, no studies have explored the changes in the vital capacity of the lungs on administering the homeopathic remedy, B. orientalis. It is shown that isometric contraction of pectoral muscles enhances the vital capacity of lungs by increasing ventilation and decreasing alveolar partial pressure of carbon dioxide. It can act as a valuable tool for monitoring the vital capacity of the lungs before and after administration of B. orientalis. AIM: This preliminary research takes the first step toward exploring vital capacity through a randomized, placebo-controlled study elucidating the effects of ongoing isometric contraction of muscles on the vital capacity of lungs of healthy individuals on the administration of B. orientalis in different potencies. It aims to compare changes in the vital capacity of lungs in healthy participants during an acute bout of isometric contraction by handgrip dynamometer after administration of B. orientalis. Materials and Methods: Eighteen participants who fulfilled the inclusion criteria gave voluntary consent to participate in this research study. The research team measured the Tmax (measured by handgrip dynamometer) and the vital capacity (measured by a vitalograph) of these participants at the baseline. The participants were then placed into three-medicine arms to administer medicine orally: Arm 1 – B. orientalis Q, Arm 2 – B. orientalis 30C, and Arm 3 – placebo, following allocation of six participants in each medicine arm. Lottery method was used for grouping participants randomly to each medicine arm. The participants were numbered from 1 to 18 using the lottery method, and it was made sure that each arm had one male and five females to have similar gender distribution. The research team blindfolded the participants with a cloth bandage (dupatta) before categorizing them into different medicine arms. The team measured each participant's Tmax and vital capacity, and then administered one dose of the assigned medicine. The team measured the Tmax and vital capacity of the participants after 10 min of administering the medicine. The process was repeated after every 24 h for 3 consecutive days. Results: The effect of ongoing isometric contractions of the skeletal muscles on the vital capacity acted as a great tool to measure improvement in vital capacity. The vital capacity of the lungs was significantly decreased after oral administration of B. orientalis Q and B. orientalis 30C, whereas there was no significant effect found in the arm that received a placebo. Conclusion: This preliminary study shows that B. orientalis decreases the vital capacity of lungs in healthy subjects and calls for further exploration of its action in higher potencies and with wider experimental parameters. Following the Law of Similimum, this inference also adds to the research scope on the potential of this homeopathic medicine in patients with restrictive lung diseases where the vital lung capacity gets significantly decreased.
Keywords: Anti‑asthmatic; Blatta orientalis; Isometric contraction; Lung capacity; Vital capacity